A 9‐month‐old with wheezing and acute hypoxic respiratory failure. Issue 5 (7th April 2019) - Wong, Matthew; Bhatia, Rajeev
Key Clinical Message: Foreign body aspiration remains a diagnostic challenge, especially in an infant. While acute onset wheezing is highly suggestive of an aspiration, wheezing carries a broad differential diagnosis resulting in frequent misdiagnoses. Many cases present with a range of nonspecific findings and normal imaging, stressing the importance of a high index of suspicion. Abstract : Foreign body aspiration remains a diagnostic challenge, especially in an infant. While acute onset wheezing is highly suggestive of an aspiration, wheezing carries a broad differential diagnosis resulting in frequent misdiagnoses. Many cases present with a range of nonspecific findings and normal imaging, stressing the importance of a high index of suspicion.